Immature Chondroid Choristoma: Clinicopathologic, Immunohistochemical, and Molecular Study of an Unusual Benign Skin Tumor. (February 2022) - Suster, David; Ronen, Shira; Mackinnon, Alexander C.; Suster, Saul
Abstract : Abstract: An unusual benign skin tumor is reported occurring in a 68-year-old woman with no significant medical history. The lesion presented as a small skin nodule in the neck. Histologic examination showed a well-circumscribed superficial dermal nodule composed of a solid proliferation of large, round cells with abundant eosinophilic cytoplasm and small centrally placed nuclei displaying a vaguely chondroid appearance. Immunohistochemical studies showed strong positivity of the tumor cells for S100 protein and vimentin and negative staining for SOX10, melanoma cocktail, HMB45, Melan-A, cytokeratin AE1/AE3, inhibin, desmin, smooth muscle actin, CD68, CD164, and neuron specific enolase. Next-generation sequencing using a panel of 50 actionable genes commonly encountered in human neoplasia did not reveal the presence of any mutations. Owing to the remarkable similarity of the lesion to immature cartilage, we consider this to be a benign tumor, most likely resulting from an embryologic defect. We propose the term immature chondroid choristoma to designate this lesion.